Insulin-induced panniculitis in a child: A rare entity - Vibhu Mendiratta; Amit Kumar Meena; Bharati Verma; Jenna Bhattacharya (Wolters Kluwer Medknow Publications, 2024)
Insulin-induced panniculitis is a rare entity. It represents the early stage of development of lipoatrophy. The complex of insulin and insulin antibodies leads to the activation of macrophages, which is responsible for the initiation of autoimmune process and leading to panniculitis followed by subsequent development of lipoatrophy. Here, we report the case of insulin-induced panniculitis with lipoatrophy associated with Type 1 diabetes mellitus in an 11-year-old female child.